Dynamics of Smartphone Addiction Among Young Children in Padang, Indonesia - Amalina Amalina; N.A. Samat; Jhoni Warmansyah (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
The increasing use of smartphones among early childhood populations has raised concerns regarding its impact on children’s development and behavior. Therefore, this study analyzes the dynamics of smartphone addiction among young children in Padang City, Indonesia, using the CSAR (Children–Susceptible–Addicted–Recovered) model. Population data and smartphone usage statistics from 2021 to 2024 were incorporated into the modeling process, while parameter estimation was conducted using a genetic algorithm with six mutation-rate variations. The best estimation result produced an error rate of 3.3646%, indicating a strong agreement between the model and empirical data. The basic reproduction number (R₀) of 0.6156 places the system in the moderate category. This suggests that although the spread of smartphone addiction among young children in Padang City is currently under control and not self-sustaining, continuous monitoring and strengthened preventive measures remain necessary to anticipate potential increases in future cases. Sensitivity analysis reveals that the transmission of addictive behavior through social interaction is the most influential factor affecting changes in R₀. These findings highlight the importance of managing peer-group interactions, such as limiting shared digital activities and strengthening collaborative non-digital play, as effective preventive strategies. Numerical simulations further support these results by demonstrating the system’s tendency toward an addiction-free equilibrium. Overall, this study provides a solid theoretical and empirical foundation for policy formulation and future research on early childhood digital behavior.